Bringing power and time in: How do the role of government and generation matter for environmental policy support? - Kim, Kyunghwan; Kim, Seoyong (Energy Strategy Reviews, 2022)
This study aims to explore the effects of power and time on support for environmental policies. We use the government's interventions and roles to reflect power and intergenerational differences to reflect time. Traditional studies focus on the political and psychological factors that determine support for environmental policies. However, they do not generally consider governmental power and generational preferences embedded in governance context and time. We analyze survey data with a focus on government's role and generational differences. Our findings show that respondents' support for the government's environmental responsibility and spending is affected by their normative perceptions of government interventions and the general role of the government, particularly its facilitative role. Additionally, we find that the significance and direction of the associations vary across generational cohorts. The findings imply that taking different approaches for different generations and establishing the government's facilitative role are necessary to induce support for environmental policies.
Keywords: Environmental attitudes; Environmental policy; Environmental policy support; Government intervention; Government roles; Intergenerational attitude; Korea; Policy support; Power; Role of government; Environmental attitude; Environmental policy support; Intergenerational attitude; Korea; Role of government